2019
DOI: 10.1186/s12903-019-0805-6
|View full text |Cite
|
Sign up to set email alerts
|

Randomized investigation of the bioavailability of fluoride in saliva after administration of sodium fluoride, amine fluoride and fluoride containing bioactive glass dentifrices

Abstract: Objectives Bioactive glasses which degrade in aqueous solutions may release bioactive ions such as fluoride (F - ) and support fluoride bioavailability in saliva. We investigated how these effects would be apparent in an in vivo experimental trial after toothbrushing in comparison with sodium fluoride and amine fluoride. Material and methods In this single-center, randomized, parallel in vivo trial with a three strata block design, where healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 46 publications
0
14
0
Order By: Relevance
“…[97] In a more thorough study, the bioavailability of fluoride ions from F-containing bioglass was found to be equivalent to those present in high concentrations of sodium fluoride and amine fluoride. [98] Layered double hydroxides (LDHs) are ionic layers with positively-charged metal plates. The layered structure provides space for ion exchange and is used extensively in drug delivery systems.…”
Section: Fluoride Deliverymentioning
confidence: 99%
See 1 more Smart Citation
“…[97] In a more thorough study, the bioavailability of fluoride ions from F-containing bioglass was found to be equivalent to those present in high concentrations of sodium fluoride and amine fluoride. [98] Layered double hydroxides (LDHs) are ionic layers with positively-charged metal plates. The layered structure provides space for ion exchange and is used extensively in drug delivery systems.…”
Section: Fluoride Deliverymentioning
confidence: 99%
“…[ 97 ] In a more thorough study, the bioavailability of fluoride ions from F‐containing bioglass was found to be equivalent to those present in high concentrations of sodium fluoride and amine fluoride. [ 98 ]…”
Section: Ion Deliverymentioning
confidence: 99%
“…Therefore, the amount of FAP formed due to th limited bioavailability of fluoride is questionable. In F-BG toothpaste, fluoride is incor porated inside its glass composition, which possibly leads to its sustained release along with other useful ions such as calcium and phosphate [28,29], leading to the formation o…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the amount of FAP formed due to the limited bioavailability of fluoride is questionable. In F-BG toothpaste, fluoride is incorporated inside its glass composition, which possibly leads to its sustained release along with other useful ions such as calcium and phosphate [ 28 , 29 ], leading to the formation of FAP and a consequent increase in surface micro-hardness. Another aspect of our surface-microhardness results was the observance of reduced enamel micro-hardness post-demineralization for all the samples and an increase in the micro-hardness post-remineralization.…”
Section: Discussionmentioning
confidence: 99%
“…Bioactive glasses (BAGs) are attractive additives for remineralizing toothpastes for treating dentine hypersensitivity [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ]. Dentine hypersensitivity is thought to occur as a result of fluid flow in open dentinal tubules that triggers nerves in the pulp chamber [ 15 ].…”
Section: Introductionmentioning
confidence: 99%